2015
DOI: 10.1186/s12936-015-0856-3
|View full text |Cite
|
Sign up to set email alerts
|

Simian malaria in wild macaques: first report from Hulu Selangor district, Selangor, Malaysia

Abstract: BackgroundMalaria is a vector-borne parasitic disease which is prevalent in many developing countries. Recently, it has been found that Plasmodium knowlesi, a simian malaria parasite can be life-threatening to humans. Long-tailed macaques, which are widely distributed in Malaysia, are the natural hosts for simian malaria, including P. knowlesi. The aim of the present study was to determine the prevalence of simian malaria parasites in long-tailed macaques in the district of Hulu Selangor, Selangor, Malaysia.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 37 publications
11
60
1
Order By: Relevance
“…A comparison with multiple studies using molecular methods to detect Plasmodium infections in macaques from other locations indicates that the prevalence of malaria and of the different species of Plasmodium vary according to the sampling site, even on a small island like Singapore [18–20, 2226]. Comparing the Singaporean samples screened from this study, which were collected from 2007, with the Singaporean samples reported from 2011 [20], there was a decrease in the prevalence of P. knowlesi infection.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with multiple studies using molecular methods to detect Plasmodium infections in macaques from other locations indicates that the prevalence of malaria and of the different species of Plasmodium vary according to the sampling site, even on a small island like Singapore [18–20, 2226]. Comparing the Singaporean samples screened from this study, which were collected from 2007, with the Singaporean samples reported from 2011 [20], there was a decrease in the prevalence of P. knowlesi infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Malaysia have shown that the long-tailed macaques harbor at least five species of simian Plasmodium [14,15], all of which have also been detected in An . balabacensis [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Because these parasites’ infections in humans are likely to originate from close proximity between humans and wild macaques, a thorough understanding of the distribution of the zoonotic malaria parasite in nature is essential in the control and prevention of malaria disease in countries and regions under high risk. Recent studies have shown that P. cynomolgi is one of the most common malarial parasites among wild cynomolgus macaques and is uniformly and widely distributed throughout cynomolgus macaque populations in Southeast Asia . Infections in experimentally infected rhesus macaques result in much more severe clinical manifestations than in cynomolgus macaques .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that P. cynomolgi is one of the most common malarial parasites among wild cynomolgus macaques and is uniformly and widely distributed throughout cynomolgus macaque populations in Southeast Asia. 38,[42][43][44] Infections in experimentally infected rhesus macaques result in much more severe clinical manifestations than in cynomolgus macaques. 36 Furthermore, previous studies reported a significantly higher count of parasites in rhesus macaques than in cynomolgus macaques within the same duration after infection.…”
Section: Introductionmentioning
confidence: 99%